Impact toughness of 12Cr1MoV steel. Part 1 – Influence of temperature on energy and deformation parameters of fracture; Theoretical and Applied Fracture Mechanics; Vol. 83: ICEAF-IV Engineering Against Failure - Panin S. V. Sergey Viktorovich; Marushchak P. O. Pavel Orestovich; Vlasov I. V. Ilya Viktorovich; Ovechkin B. B. Boris Borisovich (2016, 2016)
Title screen